Delving Into Thermoeconomics: A Brief Theoretical Comparison of Thermoeconomic Approaches for Simple Cooling Systems - Picallo-Perez, Ana; Sala, José Mª; Portillo, Luis del; Vidal, Raquel (Frontiers in Sustainability, 2021)
Thermoeconomics combines the concepts of economics and thermodynamics to assess the cost formation process of thermal systems. It has great applicability in the allocation, optimization and diagnosis of product costs. However, some aspects need to be gathered and solved, to have common criteria for its implementation. That is precisely what happens with dissipative components, which are part of cooling systems being so that different criteria are given to evaluate their impact in the cost distribution. In this paper, the state of art regarding the application of thermoeconomics in simple cooling systems is briefly evaluated, by giving the main characteristic of each approach, resolving that there is no a common criterion on the subject of the treatment of dissipative equipment and, therefore, neither on the costs accounting. Therefore, this work compiles and compares the different thermoeconomics methodologies. Consequently, it aims to serve as a tool for the appropriate selection of the thermoeconomics methodology for the analysis of real cooling systems.